Increased Organizational Commitment through Transformational Leadership, Procedural Justice, Employee Engagement, and Work Environment - Anisa, Maulida; Martono, S (Management Analysis Journal, 2019)
The purpose of this study are to determine the effect of transformational leadership, procedural justice, employee engagement, and work environment on organizational commitment. The type and design of the research used in this study is quantitative research. The population of this study is employee of the editorial department of Merdeka Press Semarang. Sampling in this study is using a saturated sampling system and obtained the sample size that must be used in this study is 124 employees. The application method of data collection using a questionnaire with a interval. The analytical method used is the test instruments (validity and reliability), hypothesis testing with SPSS 22. The results of the study show that all hypotheses are accepted. Therefore could be known that transformational leadership has a effect on organizational commitment. Procedural justice has a effect on organizational commitment. Employee engagement has a effect on organizational commitment. Work environment has a effect on organizational commitment